Examining Preservice Teachers’ Knowledge of Area Formulae - Yew, W.T.; Zamri, S.N.A.S.; Lian, L.H. (2010)
The aim of this paper was to examine preservice teachers’ knowledge of area formulae. Clinical interview technique was employed to collect the data. This paper reports the analysis of the responses of eight preservice teachers related to a particular task, Task 8. In Task 8, preservice teachers were asked to show a Form One student the way to develop area formulae of a rectangle, parallelogram, triangle, and trapezium. Findings of the study suggest that all of them lack conceptual knowledge underpinning the formula for the area of a rectangle. The implication of the finding was also discussed.